Mechanisms of Accumulation of Chemical Elements in a Peat Deposit in the Eastern Part of Vasyugan Swamp (West Siberia); Doklady Earth Sciences; Vol. 486, iss. 1 - Savichev O. G. Oleg Gennadievich; Mazurov A. K. Aleksey Karpovich; Rudmin M. A. Maksim Andreevich; Shakhova N. E. Nataljya Evgenjevna; Sergienko V. I. Valentin; Semiletov I. P. Igor Petrovich (2019, 2019)
Title screen